2001
DOI: 10.1046/j.1524-4733.2001.40201-29.x
|View full text |Cite
|
Sign up to set email alerts
|

Dg1: The Relationship of Diabetes Symptoms and Health-Related Quality of Life

Abstract: OBJECTIVES: To determine the relationship between diabetes symptom burden and patients' perceptions of health‐related quality of life (HRQL). METHODS: A questionnaire was sent to 3,716 adults with diabetes enrolled in a managed care organization in West Virginia and southeastern Ohio. Diabetes symptom burden was measured using a 17‐item scale (Diabetes TyPE, Form 2.1). The Health Status Questionaire (HSQ‐12), Version 3.0 was utilized to measure patients' perception of their HRQL. Analyses focused on six domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
5
4
0
Order By: Relevance
“…Hospital admission was usually due to hyperglycemia and increased symptoms of diabetes. Increased symptoms of diabetes are associated with a decreased HRQOL as reported by Pfalzgraf et al 23 The findings of this study were supported by Goddijn et al 28 who reported that disappearance of hyperglycemia after treatment and glycemic control were associated with improvement in HRQOL, particularly in physical functioning, social functioning, vitality and health change with the SF-36 scale. The Goddijn et al 28 study was a prospective cohort study with 94 patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hospital admission was usually due to hyperglycemia and increased symptoms of diabetes. Increased symptoms of diabetes are associated with a decreased HRQOL as reported by Pfalzgraf et al 23 The findings of this study were supported by Goddijn et al 28 who reported that disappearance of hyperglycemia after treatment and glycemic control were associated with improvement in HRQOL, particularly in physical functioning, social functioning, vitality and health change with the SF-36 scale. The Goddijn et al 28 study was a prospective cohort study with 94 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Emergency visits and hospital admissions were usually due to hyperglycemia and increased symptoms of diabetes. Increased symptoms of diabetes were found to be associated with decreased HRQOL as reported by Pfalzgraf et al 23 This was also reported by Hemingway et al 24 who found that women scored lower than men in every age group by the SF-36 in non-diabetic patients. In our study, males had higher scores than females, which was also reported by Lloyd et al, who reported that men consistently produced higher mean scores on the SF-36 than women, in 1233 type 2 diabetic patients who were not using insulin.…”
Section: Discussionsupporting
confidence: 75%
“…Emergency visits and hospim m tal admissions were usually due to hyperglycemia and increased symptoms of diabetes. Increased symptoms of diabetes were found to be associated with decreased HRQOL as reported by Pfalzgraf et al 23 This was also reported by Hemingway et al 24 who found that women scored lower than men in every age group by the SFm36 in nonmdiabetic patients. In our study, males had higher scores than females, which was also reported by Lloyd et al, who reported that men consistently produced higher mean scores on the SFm36 than women, in 1233 type 2 diabetic patients who were not using insulin.…”
Section: Discussionsupporting
confidence: 75%
“…The increasing global prevalence of type 2 diabetes (T2DM) is accompanied by increased clinical and economic burden [ 1 ]. Achieving good metabolic control, including tight control of blood glucose, contributes to reducing the clinical, psychological, and economic burden of T2DM, and this requires that healthcare professionals and patients work together to achieve optimal treatment of this chronic disease [ 2 - 5 ]. The influence of physical and social factors on T2DM incidence and health outcomes is also receiving attention [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health-related quality of life (HRQoL) of patients with diabetes is often impaired, compared with a population without diabetes, and can be affected by both clinical and psychosocial factors [ 8 , 9 ]. HRQoL is inversely correlated with diabetes severity [ 5 , 9 , 10 ], and improvements in the clinical condition of patients with diabetes, particularly T2DM, are often accompanied by improvements in HRQoL and some other related patient-reported outcomes (PROs), such as health status and psychological well-being [ 8 , 11 - 14 ]. Newer T2DM therapies such as glucagon-like peptide-1 (GLP-1) receptor agonists are typically associated with weight loss; these therapies have been associated with improvements in weight-related quality of life (i.e.…”
Section: Introductionmentioning
confidence: 99%